Strategi pemenuhan kebutuhan air bersih pada masyarakat desa ajakkang, kecamatan soppeng riaja, kabupaten barru - Fahira, Nurul; Aksa, Kamran; Rasyidi, Emil Salim (Journal of Urban Planning Studies, 2024)
Nurul Fahira. 2023. "Strategy to Meet Clean Water Needs in the Community of Ajakkang Village, Soppeng Riaja District, Barru Regency". (Guided by S. Kamran Aksa and Emil Salim Rasyidi) The main problems in this study are (1) What factors influence the unfulfilled need for Clean Water in the people of Ajakkang Village, Soppeng Riaja District, Barru Regency? (2) What is the strategy in meeting the needs of Clean Water in the Ajakkang village community? The research was conducted in Ajakkang Village, Barru Regency. Where the need for clean water in this village is needed due to the availability of minimal water sourced from wells and also poor water quality. The analysis used in this study is chi-square test analysis to determine the influencing factors and SWOT analysis to determine the direction of strategies in meeting Clean Water needs. The results of this study show that the variables of water availability and water quality have a strong effect on clean water needs, the variables of clean water facilities have a moderate effect and economic conditions have a weak effect on clean water needs. Efforts to meet clean water needs are carried out in: (a) Utilization of clean water sources derived from springs as an alternative to water sources from wells, (b) improvement of clean water purification technology against existing raw water sources. Keywords : Clean Water Needs, Fulfillment, Barru Regency